A body mass index-based method for “MR-only” abdominal MR-guided adaptive radiotherapy - Rippke, Carolin; Renkamp, Claudia Katharina; Stahl-Arnsberger, Christiane; Miltner, Annette; Buchele, Carolin; Hörner-Rieber, Juliane; Ristau, Jonas; Debus, Jürgen; Alber, Markus; Klüter, Sebastian (Zeitschrift für medizinische Physik, 2024)
Purpose - Dose calculation for MR-guided radiotherapy (MRgRT) at the 0.35 T MR-Linac is currently based on deformation of planning CTs (defCT) acquired for each patient. We present a simple and robust bulk density overwrite synthetic CT (sCT) method for abdominal treatments in order to streamline clinical workflows. - Method - Fifty-six abdominal patient treatment plans were retrospectively evaluated. All patients had been treated at the MR-Linac using MR datasets for treatment planning and plan adaption and defCT for dose calculation. Bulk density CTs (4M-sCT) were generated from MR images with four material compartments (bone, lung, air, soft tissue). The relative electron densities (RED) for bone and lung were extracted from contoured CT structure average REDs. For soft tissue, a correlation between BMI and RED was evaluated. Dose was recalculated on 4M-sCT and compared to dose distributions on defCTs assessing dose differences in the PTV and organs at risk (OAR). - Results - Mean RED of bone was 1.17±0.02, mean RED of lung 0.17±0.05. The correlation between BMI and RED for soft tissue was statistically significant (p<0.01). PTV dose differences between 4M-sCT and defCT were Dmean: −0.4±1.0%, D1%: −0.3±1.1% and D95%: −0.5±1.0%. OARs showed D2%: −0.3±1.9% and Dmean: −0.1±1.4% differences. Local 3D gamma index pass rates (2%/2mm) between dose calculated using 4M-sCT and defCT were 96.8±2.6% (range 89.9-99.6%). - Conclusion - The presented method for sCT generation enables precise dose calculation for MR-only abdominal MRgRT.